2010
DOI: 10.1029/2010wr009071
|View full text |Cite
|
Sign up to set email alerts
|

Values of natural and human‐made wetlands: A meta‐analysis

Abstract: [1] The values of goods and services provided by wetland ecosystems are examined through a meta-analysis of an expanded database of wetland value estimates and with a focus on human-made wetlands. This study extends and improves upon previous meta-analyses of the wetland valuation literature in terms of the number of observations, geographical coverage, wetland class and integrity, and the measurement of the effects of scarcity and anthropogenic pressure. We find that water quality improvement, nonconsumptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(126 citation statements)
references
References 58 publications
(79 reference statements)
2
120
1
3
Order By: Relevance
“…Similar results were found, where water quality improvement was among the three highest valued ecosystem services of wetlands [24]. Studies have shown that wetlands properly constructed and maintained could be effective for protecting water quality [25,26].…”
Section: Resultssupporting
confidence: 74%
“…Similar results were found, where water quality improvement was among the three highest valued ecosystem services of wetlands [24]. Studies have shown that wetlands properly constructed and maintained could be effective for protecting water quality [25,26].…”
Section: Resultssupporting
confidence: 74%
“…They estimated worldwide reactive nitrogen removal by wetlands to be approximately 17% of anthropogenic nitrogen inputs, though they did not explore the role of wetland size on nutrient processing. A meta-analysis of 186 wetland sites, however, found a negative correlation between wetland size and water quality [Ghermandi et al, 2010]. Further, in a review of 17 constructed wetlands receiving agricultural runoff in Europe, Braskerud et al [2005] found specific particulate phosphorus retention (g P retention/m 2 /year) to decrease as wetland area increased.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Useful summaries and meta-analyses of the valuation literature on forests are provided by Barrio and Loureiro (2010), Lindhjem (2007), Ojea et al (2010), Zanderson and Tol (2009); and on wetlands by Brander et al (2006Brander et al ( , 2012, Brouwer et al (1999), Ghermandi et al (2010) and Woodward and Wui (2001). Descriptive overviews of the valuation literature on natural open space proximate to urban areas are provided in Fausold and Lilieholm (1999) and McConnell and Walls (2005).…”
Section: Introductionmentioning
confidence: 99%